2013
DOI: 10.1016/j.bpj.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Challenge Drives Rapid and Reversible Chromatin Condensation in Chondrocytes

Abstract: Changes in extracellular osmolality have been shown to alter gene expression patterns and metabolic activity of various cell types, including chondrocytes. However, mechanisms by which physiological or pathological changes in osmolality impact chondrocyte function remain unclear. Here we use quantitative image analysis, electron microscopy, and a DNase I assay to show that hyperosmotic conditions (>400 mOsm/kg) induce chromatin condensation, while hypoosmotic conditions (100 mOsm/kg) cause decondensation. Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 48 publications
12
125
0
1
Order By: Relevance
“…Functional expression of TRPV4 and PIEZO1/2 (and potentially other channels) (55,56) in articular chondrocytes allow cells to respond to the continuum of mechanical loads in cartilage. The findings of this study, together with those in the literature, suggest that chondrocyte mechanosensation involves an integrated set of pathways that may also include transmission of pericellular mechanical and osmotic signals to the cell and nucleus via integrins and various cytoskeletal components (17,(57)(58)(59)(60)(61).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Functional expression of TRPV4 and PIEZO1/2 (and potentially other channels) (55,56) in articular chondrocytes allow cells to respond to the continuum of mechanical loads in cartilage. The findings of this study, together with those in the literature, suggest that chondrocyte mechanosensation involves an integrated set of pathways that may also include transmission of pericellular mechanical and osmotic signals to the cell and nucleus via integrins and various cytoskeletal components (17,(57)(58)(59)(60)(61).…”
Section: Discussionsupporting
confidence: 56%
“…Although many different mechanisms have been shown to be involved in chondrocyte mechanotransduction (13,(15)(16)(17), recent studies show that the cation channel, TRPV4, is responsible for mediating the anabolic response of chondrocytes to osmotic or mechanical stress (18)(19)(20). In this regard, identification of the mechanosensitive pathways involved in cartilage homeostasis as well as injury will help to provide novel targets for rational treatment of cartilage injury and posttraumatic osteoarthritis (21).…”
mentioning
confidence: 99%
“…However, the mechanical forces influencing the shape of the nucleus in live cells are not fully understood. Recently, factors affecting nuclear shape have been identified in yeast and Arabidopsis (Laporte et al, 2013;Tamura et al, 2013), and external osmotic pressures have been shown to change cell and nuclear volumes of chondrocytes by ±50% in both 2D and 3D cultures (Irianto et al, 2013). Here, we quantitatively examine forces shaping the nucleus using a combination of experiments and physical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Culturing MSCs on stiff substrate also increases the protein levels of cytoskeletal components, consistent with greater activity of serum response factor (SRF) (Connelly et al, 2010;Ho et al, 2013), and, in combination with a stiffer nucleus, this further increases cytoskeletal tension. Translocation of molecular signal carriers is a recurring motif in mechanosensitive pathways that has been shown to occur during the transfer of ions and changes in osmotic pressure (Finan et al, 2009;Irianto et al, 2013;Kalinowski et al, 2013), as well as during the migration of protein factors. Protein translocation could be driven by a change in the concentration of binding sites, (e.g.…”
Section: Mechanotransduction To the Nucleus -Downstream Of Ecm And Laminmentioning
confidence: 99%